Upaya Deteksi Dini Tumbuh Kembang Anak Pra Sekolah Melalui Pemantauan Status Gizi - Yuliana Noor Setiawati Ulvie; Addina Rizky Fitriyanti; Alifya Firda Zulfa (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2026)
Issues relating to undernutrition, stunting, and overnutrition remain public health challenges that can affect children’s growth and development. Therefore, efforts are needed to ensure early detection and raise awareness of the importance of monitoring children’s nutritional status. The objective of this community service activity was to determine the nutritional status of young children through anthropometric measurements of pupils at 20. The activity was carried out using a participatory approach through the stages of planning, coordination, anthropometric measurement, and data analysis, involving 952 children. Measurements included weight, height, upper arm circumference (UAC), and anthropometric index assessments based on WHO standards. Based on UAC measurements, almost all children fell into the ‘good nutrition’ category. Based on height-for-age, many children had normal height, although some children were still classified as short or very short, and some children were underweight, malnourished, or overweight, even obese. These findings indicate the existence of a double burden of malnutrition among young children. This initiative helps detect nutritional problems in young children at an early stage and raises awareness among schools and parents regarding the importance of regular growth monitoring. The results of this initiative can serve as a basis for developing nutritional interventions to support optimal child growth and development.